2018
DOI: 10.1007/s42107-018-0079-3
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake recurrence effect on the response reduction factor of steel moment frame

Abstract: In this study, the effect of earthquake recurrence on the response modification factor (R factor) has been investigated. The response reduction factor of structures is one of the most important parameters for reducing the design force caused by earthquakes. An earthquake recurrence is a phenomenon caused by the accumulation of energy in faults and their continuous rupture. Given the release of energy in the faults, it is clear that the occurrence of an earthquake does not occur only once. It will often be acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Herein it was observed that under almost half of nearfield records, ground motion records caused the low-rise archetype to collapse which is contradictory to the previous research [41] where these structures completely survived under the ground motion intensity at 3.0 g. On the other hand, under far-field ground motion records it was reported that all the structures experienced collapse when the ground motion intensity reached 3.0 g, while herein the probability of collapse for low-rise building was nearly 30% and for mid-to-high rise buildings they were around 90%. In a study conducted by Abdollahzadeh, Sadeghi [42] on the seismic performance factors of 5-, 10, 15-story IMRFs using Young's method, the results indicated that on average the response modification factor around 5.5 can be acceptable, while in this study it is proofed that, the response modification factor of 5.0 is not acceptable for IMRF system subjected to near-field ground motion records using FEMA P695 methodology. On the other hand, for response modification factor of regular ductile structures a conservative value of 6.5 was proposed by Ferraioli et al [43], while herein this value is increased to 7.5.…”
Section: Discussionmentioning
confidence: 52%
“…Herein it was observed that under almost half of nearfield records, ground motion records caused the low-rise archetype to collapse which is contradictory to the previous research [41] where these structures completely survived under the ground motion intensity at 3.0 g. On the other hand, under far-field ground motion records it was reported that all the structures experienced collapse when the ground motion intensity reached 3.0 g, while herein the probability of collapse for low-rise building was nearly 30% and for mid-to-high rise buildings they were around 90%. In a study conducted by Abdollahzadeh, Sadeghi [42] on the seismic performance factors of 5-, 10, 15-story IMRFs using Young's method, the results indicated that on average the response modification factor around 5.5 can be acceptable, while in this study it is proofed that, the response modification factor of 5.0 is not acceptable for IMRF system subjected to near-field ground motion records using FEMA P695 methodology. On the other hand, for response modification factor of regular ductile structures a conservative value of 6.5 was proposed by Ferraioli et al [43], while herein this value is increased to 7.5.…”
Section: Discussionmentioning
confidence: 52%
“…Several researchers applied this technique in the field of engineering as follows: using neural network in constituent modeling of plain concrete, advanced composites, strain softening material models in reinforced concrete, structural behavior of materials relative to velocity, and material hysteresis behavior. [15,32,33] A given concept is developed for applying circular modeling. [34,35] Figure 2 shows a nonlinear hysteresis neural network, which is suggested by Yun et al [35] The presented neural network model contains five input variables, ξ n , σ n − 1 , ε n , ε n − 1 , andΔη ε, n , as strain controls.…”
Section: The Neural Network Modelmentioning
confidence: 99%
“…It is very important to estimate initial stiffness with moment-rotation response in baseplate connections, supporting frame analysis and designing. [13][14][15][16][17][18][19] Generally, correct modeling of connections behavior, which is shown as…”
mentioning
confidence: 99%
“…The final moment-rotation curve is obtained by superposition of the response of three sets of springs. Abdollahzadeh and Ghobadi [20] offered a mathematical model based on the component method for representing the complex behavior of column-base connections.…”
Section: Component-based Modeling and Existing Mechanical Modelsmentioning
confidence: 99%